Clinical profile and outcome of COVID-19-positive children in a tertiary care centre of North-East India - Aditi Baruah; Dilip M. Chowdhary; Pritikar Dowerah; Kumari Naina (Hygeia Press di Corridori Marinella, 2024)
Introduction: COVID-19 infection is said to be generally a milder disease in children, compared to adults, and is associated with much lower case-fatality rates. Objective of this study was to find out the clinical characteristics and outcome of COVID-19-positive children and also the differences between the first and the second waves, if any. Methodology: This was a retrospective study done in the Department of Paediatrics of a tertiary care teaching hospital. Departmental and hospital medical records were reviewed to assess the clinical characteristics, disease severity and outcome of all COVID-19-positive admitted children from May 2020 to September 2021 (the first wave from May 2020 to January 2021 and the second wave from April 2021 to September 2021). Data analyses were done in Microsoft® Excel® 2010.  Results: Out of total 560 COVID-19-positive children attending the hospital during the study period, 266 children (76 in the first wave and 190 in the second wave) were admitted. The majority of the children (25%) were in the age group of 1-6 months during the first wave, while in the second wave the majority of the children (27.9%) were in the age group of 5-10 years. The most common presenting complaint was fever (51.1%), followed by cough (13.9%). Co-morbidities were present in 23.3% of cases. Asymptomatic, mild, moderate, severe and critical cases were 16.5%, 51.9%, 18.4%, 6.4% and 6.8%, respectively. The case fatality ratio was 3.75% (21/560) among all positive cases. Ventilator support was required in only 10.1% of cases. There were some significant differences between the 2 waves regarding age distribution, disease severity, outcome and some presenting complaints. Conclusions: The majority of the COVID-19 infections were either asymptomatic or of mild variety. Males suffered more than females. The admission rate was higher in the second wave but death was higher in the first wave, indicating higher infectiousness and milder nature of the disease in the second wave. Most of the deaths occurred within 24 hours of admission, indicating that late admission may be an important risk factor for mortality. Except for age distribution, severity and outcome, other parameters were comparable between the first and the second wave.